Peningkatan Hasil Belajar Dalam Menganalisis Hubungan Komponen Ekosistem Menggunakan Model Pembelajaran Problem Based Learning Pada Peserta Didik Kelas V - Entiowati, Entiowati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve learning outcomes in analyzing the relationship between ecosystem components using the problem-based learning (PBL) model in class v students. This research is a classroom action research (PTK) which is carried out in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were students of class V SD Lomanis 01 in the 2020/2021 academic year, totaling 28 students. Data collection techniques using observation and tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the application of the problem-based learning model can improve student learning outcomes in the material of analyzing the relationship of ecosystem components in class V SD Negeri Lomanis 01 in the academic year 2020/2021 as evidenced by the percentage of learning outcomes completeness in cycle I of 43% to 92% in the cycle II.